Screening for REEP1 Mutations in 31 Chinese Hereditary Spastic Paraplegia Families - Ma, Xinran; He, Ji; Liu, Xiaoxuan; Fan, Dongsheng (Frontiers in Neurology, 2020)
Background: REEP1 is a common cause of autosomal dominant hereditary spastic paraplegia (HSP) but is rare in China. The pathological mechanism of REEP1 is not fully understood. Methods: We screened for REEP1 mutations in 31 unrelated probands from Chinese HSP families using next-generation sequencing targeting pathogenic genes for HSP and other related diseases. All variants were validated by Sanger sequencing. The proband family members were also screened for variants for the segregation analysis. All previously reported REEP1 mutations and cases were reviewed to clarify the genetic and clinical features of REEP1-related HSP. Results: A pathogenic mutation, REEP1c. 125G>A (p.Trp42*), was detected in a pure HSP family from North China out of 31 HSP families (1/31). This locus, which is located in the second hydrophobic domain of REEP1, is detected in both Caucasian patients with complicated HSP phenotypes and Chinese pure HSP families. Conclusion: REEP1-related HSP can be found in the Chinese population. The 42nd residue is a novel transethnic mutation hotspot. Mutations in this spot can lead to both complicated and pure form of HSP. Identification of transethnic hotspot will contribute to clarify the underlying pathological mechanisms.